2021
DOI: 10.3390/nu13072465
|View full text |Cite
|
Sign up to set email alerts
|

Effects of DHA-Rich n-3 Fatty Acid Supplementation and/or Resistance Training on Body Composition and Cardiometabolic Biomarkers in Overweight and Obese Post-Menopausal Women

Abstract: Resistance training (RT) and n-3 polyunsaturated fatty acids (n-3 PUFA) supplementation have emerged as strategies to improve muscle function in older adults. Overweight/obese postmenopausal women (55–70 years) were randomly allocated to one of four experimental groups, receiving placebo (olive oil) or docosahexaenoic acid (DHA)-rich n-3 PUFA supplementation alone or in combination with a supervised RT-program for 16 weeks. At baseline and at end of the trial, body composition, anthropometrical measures, blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 85 publications
(148 reference statements)
0
31
0
1
Order By: Relevance
“…These articles included 2438 participants (1660 females, 778 males). Fifteen studies included were randomized controlled trials [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], while one was a randomized, non-controlled trial [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These articles included 2438 participants (1660 females, 778 males). Fifteen studies included were randomized controlled trials [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], while one was a randomized, non-controlled trial [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The average age of the participants was 69.1 years. Seven studies involved females only [ 29 , 31 , 32 , 34 , 35 , 41 , 42 ], one study involved males only [ 37 ], while the remainder included both males and females [ 27 , 28 , 30 , 33 , 36 , 38 , 39 , 40 ]. Nine studies involved untrained individuals [ 27 , 28 , 29 , 33 , 37 , 38 , 40 , 41 , 42 ], one involved recreationally active participants [ 35 ], and six did not report the activity levels of the participants [ 30 , 31 , 32 , 34 , 36 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferucci et al [37] observed that both EPA and DHA demonstrated anti-inflammatory effects and were inversely associated with IL-6 and TNFα but positively associated with IL-10 concentrations. Recently, Felix-Soriano et al [38] demonstrated that supplementation with a DHA-rich fish oil concentrate had beneficial effects on cardiometabolic health markers in postmenopausal women. In our study, the adherence to dietary recommendations concerning PUFA was better in the diet of the elderly in the LGI group compared to those in the HGI group.…”
Section: Discussionmentioning
confidence: 99%